Artificial Intelligence in FMCG Retail Sector - Yovcheva, Irina (Research Papers, 2023)
The paper presents theoretical research on the diffusion of artificial intelligence (AI) in FMCG. As a result, the four main areas of AI innovation were discovered: customer experience, logistics, manufacturing, and business model. The relationship of AI with the proven technology for customer relationship management – CRM – is also revealed. Current benefits and opportunities for future optimizing business processes through digital transformation are indicated. Emphasis is placed on machine learning. Examples of using artificial intelligence among leading companies in the FMCG sector are given, as well as an example of service transformation in a supermarket in Germany during Covid-19, etc.
Keywords: Digital transformation; Artificial intelligence; FMCG retail sector